Exploring Anti-LGBT homicide by mode of victim selection - Gruenewald, Jeff (Criminal justice and behavior, 2014)
This study extends previous research by comparatively examining variations in situational circumstances of bias homicide targeting lesbian, gay, bisexual, and transgender (LGBT) victims. Rather than conceptualize categories of homicide by offender motive, this study disaggregates anti-LGBT homicide based on observable characteristics of victim selection by offenders. Anti-LGBT homicides are conceptualized as predatory and responsive offenses, which capture planned, unprovoked homicides and unplanned crimes in which victims play a role in the escalation of violence. Further situational distinctions are conceptualized within these categories of anti-LGBT homicide, and comparative analyses reveal important differences across these situational circumstances. Considering the large amount of variation found within anti-LGBT homicide, which often goes unrecognized by studies relying on official bias crimes data, these findings suggest that open-source crime data and nuanced examinations of anti-LGBT homicide may be useful tools for fashioning informed policy discussions of victim-based legal protections and law enforcement responses to bias crime.